2013
DOI: 10.1371/journal.pone.0061582
|View full text |Cite
|
Sign up to set email alerts
|

Two's a Crowd: Phenotypic Adjustments and Prophylaxis in Anticarsia gemmatalis Larvae Are Triggered by the Presence of Conspecifics

Abstract: Defence from parasites and pathogens involves a cost. Thus, it is expected that organisms use this only at high population densities, where the risk of pathogen transmission may be high, as proposed by the "density-dependent prophylaxis" (DDP) hypothesis. These predictions have been tested in a wide range of insects, both in comparative and experimental studies. We think it pertinent to consider a continuum between solitarious and gregarious living insects, wherein: (1) solitarious insects are those that are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 55 publications
2
26
2
1
Order By: Relevance
“…The density‐dependent prophylaxis hypothesis proposes that organisms should up‐regulate their defences at moments of high population density when the likelihood of being infected by horizontally‐transmitted pathogens is higher (Wilson & Reeson, ; Reynolds et al ., ). In line with previous studies, we have found support for this hypothesis in the velvetbean caterpillar: when reared at a higher population density, these were darker and more resistant to an entomopathogenic virus than green ones (Silva et al ., ). However, to date, the underlying mechanisms of such resistance have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The density‐dependent prophylaxis hypothesis proposes that organisms should up‐regulate their defences at moments of high population density when the likelihood of being infected by horizontally‐transmitted pathogens is higher (Wilson & Reeson, ; Reynolds et al ., ). In line with previous studies, we have found support for this hypothesis in the velvetbean caterpillar: when reared at a higher population density, these were darker and more resistant to an entomopathogenic virus than green ones (Silva et al ., ). However, to date, the underlying mechanisms of such resistance have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 97%
“…To avoid pseudoreplication, only one caterpillar from a given pot was ever used. Caterpillars were kept at these population densities as a way to stimulate their colour phenotypic changes (Silva et al, 2013). Thus, lone-reared caterpillars usually keep the green phenotype, whereas changes in colour (like black) are more often in group-reared caterpillars.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Por conseguinte, conforme Lemaire (2002), é geralmente observado o hábito gregário, caracterizado pela aglomeração de centenas de indivíduos, formando manchas escuras em troncos ou galhos de árvores frutíferas, em lagartas da família Saturniidae, como L. obliqua e P. cynthia, bem como em lagartas da família Noctuidae, como A. gemmatalis, que no entanto, são consideradas um estágio transitório da evolução de polifenismo de fase, uma vez que suas agregações variam de acordo com a densidade de suas populações (Silva et al 2013). …”
Section: Ausência Dos Genes Da Catepsina E Quitinase No Genoma De Loounclassified